2019
DOI: 10.15406/ijmboa.2019.04.00118
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric temporal bone langerhans cell histiocytosis: report of 2 cases with review of literature

Abstract: Introduction:Langerhans cell histiocytosis is a rare multiorgan disorder, commonly seen in the pediatric age group. Commonest presentation of the disease involving the temporal bone is ear discharge. This entity is often underdiagnosed and the patient is treated with multiple courses of antibiotics which leads to delay in diagnosis and initiating apropriate treatment. Case report:We present case reports of 2 children who presented to us with this rare disease. The line of management followed is discussed brief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The characteristic feature in CT scan includes diffusely destructive lytic bony lesions at the ear canal, mastoid process, posterior and lateral semicircular canal, but rarely involve ossicular chain, facial canal, and petrous apex. 3,[5][6][7]10 A typical "punched-out lesion" at the ear canal and squamous part of the temporal bone is characteristic as per this case. 5 Zheng et al hypothesized that the ossicular chain is resistant to granulation tissue of LCH and ossicles destruction likely contributed by existing chronic otitis media.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The characteristic feature in CT scan includes diffusely destructive lytic bony lesions at the ear canal, mastoid process, posterior and lateral semicircular canal, but rarely involve ossicular chain, facial canal, and petrous apex. 3,[5][6][7]10 A typical "punched-out lesion" at the ear canal and squamous part of the temporal bone is characteristic as per this case. 5 Zheng et al hypothesized that the ossicular chain is resistant to granulation tissue of LCH and ossicles destruction likely contributed by existing chronic otitis media.…”
Section: Discussionmentioning
confidence: 61%
“…LCH is more commonly seen in boys than females in a ratio of 2:1. 6,7 There is no specific clinical manifestation that is pathognomonic for temporal bone LCH, it depends on the site and extension of the disease. Our case presented with recurrent refractory otorrhea and aural polyp, which correlate with findings of Fernandez et al and Skoulakis et al However, recent literature reported most common manifestations are temporal bone lesion or mastoid swelling (74.1%), periauricular swelling (44.4%), otorrhea (33.3%), otalgia (22.2%) and conductive hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations